Mediated mobilities. (April 2014) - Keightley, Emily; Reading, Anna
In this article we introduce the themed issue 'Mediated Mobilities'. We begin by articulating some of the potential relationships between media and mobility critically addressing the key conceptual distinctions that underpin them and the methodological demands placed on media studies when exploring the complex ways in which mobility is embedded in contemporary media ecologies. In the first instance we consider precisely what is meant by mobility, and, more specifically, interrogate the dynamic relationship between mediated mobility and immobility. We then move on to develop a methodological framework or agenda for research on mediated mobilities. This framework traces how existing analytical trajectories in media studies research need to be developed and synthesized in order to be able to account for the multiple modes of mobility facilitated by media technologies, texts, institutions and audiences. In the last part of the article we examine the development of innovative methodologies and forms of analysis that give emphasis to movement and trajectory, but also human and algorithmic agency.